ANALISIS KINERJA KEUANGAN PADA PERUSAHAAN UTAMA JASA TRANSPORTASI YANG ADA DI BURSA EFEK INDONESIA SEBELUM DAN SAAT PANDEMI PERIODE 2018-2021 (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2023)
The purpose of this study was to determine the financial performance of the main transportation service companies on the Indonesia Stock Exchange for the 2018-2021 period. The population and samples are taken based on certain criteria or purposive sampling. This study uses quantitative data analysis from secondary data obtained from audited financial reports. The results of the study can be concluded that when viewed from the aspect of the pre-pandemic activity ratio it was much better during the pandemic, with the highest average receivables turnover ratio in 2018 of 15.46 times. The liquidity ratio during the pandemic was much better than before the pandemic with an average working capital ratio of 328,873,000,000, a current ratio of 2.02 times, a quick ratio of 1.46 times and a cash ratio of 83.42% in 2021. If you look at it from Profitability and solvency ratios have fluctuated. This indicates that the financial performance of the main transportation service company is not optimal.
Keywords: Financial Performance; Financial Ratios; and Financial Statements.